1983
DOI: 10.1128/jvi.48.3.627-632.1983
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of bluetongue virus neutralization

Abstract: Molecular and serological analyses of bluetongue virus serotypes 10 and 11 and their intertype reassortants indicate that the viral RNA segment L2 codes for the serotype-specific antigen. Individual RNA segments of parental and reassortant viruses were characterized by oligonucleotide fingerprint analyses. Analyses of their virion polypeptides by Cleveland peptide mapping (Cleveland et al., J. Biol. Chem. 252:1102-1106, 1977) demonstrated that the L2 gene segregated colinearly with the viral P2 protein, implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(33 citation statements)
references
References 14 publications
(20 reference statements)
3
30
0
Order By: Relevance
“…BTV-10 VP2 protein, in excess of 50 ,ug per sheep, elicited neutralizing antibodies and totally protected the animals. These results confirmed previous observations that the outer capsid protein VP2 is the main determinant of the neutralization-specific immune response (1,10,11,13,14) and that it induces protection (11). Our data indicated that 50 ,ug of the expressed VP2 alone was insufficient to confer total protection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…BTV-10 VP2 protein, in excess of 50 ,ug per sheep, elicited neutralizing antibodies and totally protected the animals. These results confirmed previous observations that the outer capsid protein VP2 is the main determinant of the neutralization-specific immune response (1,10,11,13,14) and that it induces protection (11). Our data indicated that 50 ,ug of the expressed VP2 alone was insufficient to confer total protection.…”
Section: Discussionsupporting
confidence: 92%
“…Using immunoprecipitation techniques, Huismans and Erasmus (10) have shown that VP2 is a major serotype-specific antigen. This has been confirmed by analyzing intertypic reassortant viruses (14). Huismans and associates (11) demonstrated that VP2 polypeptide recovered from purified BTV induced neutralizing antibodies and protected sheep against virulent viral challenge, indicating the potential of using VP2 as a subunit vaccine.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The BTV genome encodes for seven structural (VP1 to VP7) and five non-structural proteins (NS1 to NS5) [2,3]. BTV serotype identification primarily relies on the serum neutralisation test, which is based on specific interactions between neutralising antibodies, generated during infection of the host, and the viral VP2 protein located on the outer capsid [4,5]. Based on the serum neutralisation test and/or phylogenetic analysis of VP2, which is the most variable protein, several novel BTV serotypes have been identified [6] in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…BTV is a double‐capsid virus with a genome of 10 double‐stranded RNA segments encoding seven structural [viral protein 1 (VP1) to VP7] and five non‐structural proteins (Mertens et al., ; Ratinier et al., ). Serotype of BTV is recognized based on specific interactions of neutralizing antibodies (NA) with proteins displayed on the outer capsid of the virus (Huismans and Erasmus, ; Kahlon et al., ). VP2, protein of the outer capsid, is the most variable BTV protein and is considered the major serotype‐defining protein of BTV able to induce the production of neutralizing antibodies (NA) (Shaw et al., ).…”
Section: Introductionmentioning
confidence: 99%